MAGNETIZATION AND INTRAGRAIN CRITICAL CURRENT-DENSITY OF MONOPHASIC TL1.8BA2CA2.2CU3O10-DELTA - Liu, R; Johnson, J; Edwards, P; Campbell, A (1991)
Monophasic Tl2Ba2Ca2Cu3O10 has been prepared using the stoichiometric composition Tl1.8Ba2Ca2.2Cu3O10-δ. Superconductivity in the compound Tl1.8Ba2Ca2.2Cu3O10-δ occurs below 120 K as measured by electrical resistivity and magnetisation. The intragrain critical current density is estimated to be 6.75 × 106 A/cm2 at T = 5 K and H = 1 T in Tl1.8Ba2Ca2.2Cu3O10-δ. © 1991.